Fracture types in the lower Cambrian shale and their effect on shale gas accumulation, Upper Yangtze. (January 2019) - Zhang, Yuying; He, Zhiliang; Jiang, Shu; Lu, Shuangfang; Xiao, Dianshi; Chen, Guohui; Li, Yuchao
Abstract: To reveal the characteristics of fractures in high quality shale reservoir and to find regions that are favorable for shale gas accumulation, the characteristics of fractures and their effect on the shale gas content in the lower Cambrian marine shale from 2 typical shale gas wells in the Upper Yangtze have been analyzed in detail by observing the shale cores, scanning electron microscope photographs and rock slice pictures associated with various geochemical data. Five types of macrofractures (high-angle shearing fracture, tension-shearing fracture, compresso-shearing fracture, low-angle slip fracture, and bedding fracture) and 4 types of microfractures (interlayer fracture, inter-particle fracture, intra-particle fracture, and organic matter-associated fracture) have been identified in the lower Cambrian shale. The fractures in lower Cambrian shale have 5 possible origins: 1 generated by tectonic tension and shearing stresses; 2 cracking due to loading pressure relief; 3 corroded by acidic fluids during hydrocarbon generation; 4 induced by overpressured fluid; 5 formed due to diagenesis-associated shrinkage of mineral crystals. In general, the shale in Sichuan Basin contains more nonstructural fractures (including bedding fractures and microfractures), whereas shale outside the basin contains more structural fractures (including high-angle shearing fractures, tension-shearing fractures, and low-angle slip fractures). Three controlling factors of fracture development be summarized as follows: 1 tectonic setting; 2 mineral components; 3 organic matter content and maturity. In conclusion, structural fractures can be considered as destructive, and nonstructural fractures can be considered as favorable. Shale gas reservoirs can be divided into 3 types: type A with a shale gas content >2 m 3 /t, destructive/structural fractures <20/m, and favorable/nonstructural fractures >100/m; type B with a shale gas content of 1 m 3 /t - 2 m 3 /t, destructive/structural fractures <20/m, and favorable/nonstructural fractures 50/m −100/m; (3) type C with a shale gas content < 1 m 3 /t, destructive/structural fractures >20/m, or destructive/structural fractures <20/m, and favorable/nonstructural fractures <50/m. Highlights: 5 types of macrofractures and 4 types of microfractures have been identified. The fractures in lower Cambrian shale might have 5 possible origins. Fracture effecters: tectonic setting, mineral components, organic matter content and maturity. Shale gas reservoir could be divided into 3 types based on fracture density and gas content.